2013
DOI: 10.1371/journal.pone.0073584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adult Exposure to Bisphenol A on Genes Involved in the Physiopathology of Rat Prefrontal Cortex

Abstract: Several neurological and behavioral dysfunctions have been reported in animals exposed to bisphenol A (BPA). However, little is known about the impact of adult exposure to BPA on brain physiopathology. Here, we focused on prefrontal cortex (PFC) of rats, because it is an important area for cognitive control, complex behaviors and is altered in many psychopathologies. Gamma-aminobutyric acid (GABA) and serotonin (5-HT) systems are essential for PFC function. Therefore, we examined the effects of adult exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 61 publications
2
21
1
Order By: Relevance
“…In this work, BPA decreased 5α-R2 mRNA and protein levels without affecting 5α-R1 expression, which differs from our previous findings in adult rats treated for four days with 50 mg BPA/ kg/d (Castro et al, 2013b). These discrepancies may reflect temporal or compensatory effects as a result of differential exposure times, or dose-dependent mechanisms (Vandenberg et al, 2012).…”
Section: Effects On 5α-r Isozymescontrasting
confidence: 99%
See 2 more Smart Citations
“…In this work, BPA decreased 5α-R2 mRNA and protein levels without affecting 5α-R1 expression, which differs from our previous findings in adult rats treated for four days with 50 mg BPA/ kg/d (Castro et al, 2013b). These discrepancies may reflect temporal or compensatory effects as a result of differential exposure times, or dose-dependent mechanisms (Vandenberg et al, 2012).…”
Section: Effects On 5α-r Isozymescontrasting
confidence: 99%
“…3α,5α-NS modulate emotional responses and cognitive function (Frye, 2009;Paris et al, 2011b), which are mediated in part by the PFC (Davidson, 2002;Paris et al, 2011b). With this in mind and the finding that short-term exposure to BPA affects 5α-R levels in the PFC of adult female rats (Castro et al, 2013b), we believe that this enzyme might be a potential target for BPA-mediated effects in the female perinatal brain.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, our present demonstration of BPA stimulation of aromatase expression may have significant implications for the function of estrogens during pregnancy. Although our present findings are in contrast to those reported previously of decreased aromatase activity and expression in JEG-3 cells [33,35], they are consistent with those of numerous in vitro and in vivo studies [48][49][50][51][52][53][54][55]. For example, BPA exposure has been shown to increase aromatase expression in the rat brain [50,53], ovary [51] and prostate [54].…”
Section: Discussionsupporting
confidence: 87%
“…Recent findings regarding BPA neurotoxicity have indicated that this endocrine disruptor produces brain region-specific changes in dopaminergic processes, resulting in hyperactivity, attention deficits, and a heightened sensitivity to drugs of abuse (Jones and Miller, 2008;Narita et al, 2006). Moreover, we and others have pointed out that BPA might also affect the serotoninergic system (Castro et al, 2013;Matsuda et al, 2010Matsuda et al, , 2013.…”
Section: Introductionmentioning
confidence: 87%